DEVELOPMENT OF PRODUCTION POTENTIAL OF TOURISM BUSINESS IN EU COUNTRIES - KUPALOVA, Halina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Tourism entrepreneurship in a modern post-industrial society is an important component of the economy of Ukraine, as it allows the development of adjacent areas of production, contributes to regional development through the creation of additional jobs, employment of the population, and tax revenues. With Ukraine obtaining the status of a candidate for membership in the European Union, there is a need to analyze the evolution of tourism entrepreneurship in European countries, predict the scale of development of its production potential in the coming years. At the same time, first of all, it is advisable to clarify the understanding of the production potential of entrepreneurship essence from the point of view of theory. The purpose of the article is to clarify the essence, identify the main trends and calculate the forecast indicators of the tourism entrepreneurship production potential development in the EU countries, taking into account which will contribute to the accelerated integration of Ukraine into the international market of tourist services. The article discusses modern approaches to the interpretation of the "production potential" concept. The expediency of using the resource approach to the assessment of the production potential development of tourism entrepreneurship is substantiated. The structure of the production potential of tourism entrepreneurship of the EU was analyzed. The trends of changes in the structure of the tourism entrepreneurship production potential in the EU during 2011–2020 have been determined. The ranking of European countries by the growth rate of the total number of beds in tourist accommodations in 2011–2020 was carried out. With the help of VAR modeling, a forecast of the production potential development of the EU tourism business until 2030 was made.